Selecting foreign markets in SME companies in the plastics sector in Medellin, Colombia [Selección de mercados extranjeros en empresas PYME del sector del plástico en Medellín, Colombia] (2016)
The purpose of this article is to identify the profiles of internationalization of a representative sample of companies in the plastics sector SMEs, located in Medellin, Colombia. For this, the software resulting from the study entitled International Business and Innovation, attached to the research group and business and international relations at the University of Medellin was validated. As a result a number of choices of countries are presented to the surveyed organizations to select their internationalization.